Addition and Subtraction of Fractions Module Based Project Based Learningfor Students of Elementary School - Triwahyuningtyas, Dyah; Mahmuda, Novia Eka; Santoso, Lidya Ristanti; Sesanti, Nyamik Rahayu (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
Independent teaching materials in the form of modules containing an understanding of mathematical concepts need to be further developed on a project-based basis. Therefore, the purpose of this study was to develop a module for adding and subtracting fractions based on Project-Based Learning (PjBL) for the fourth grade of elementary school. This research applies Thiagarajan 4D research and development methods (Define, Design, Develop, and Disseminate). The data analysis technique used is descriptive qualitative and quantitative analysis. The results of the research on the development of the Project Based Learning -based fraction addition and subtraction module were declared feasible and effective to be applied in elementary schools. The implementation of PjBL-based modules in elementary schools shows a positive response from students and students' understanding of the addition and subtraction of fractions is increasing.